The poodle and the pea - Guillain, Charlotte; Andersen, H C (Chicago, Ill Raintree, 2013)
A simplified version of the familiar tale featuring a young poodle who has been lost in the woods then finds shelter in a palace where, by feeling a pea through many blankets, she proves that she is a real princess. Includes a note on the history of the tale
A gift from book Africa
English stories
1 2 13
Keywords: Fairy tales; Folklore